2000
DOI: 10.2136/sssaj2000.642543x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Structural Form during Infiltration Laboratory Measurements on the Effect of De‐inking Sludge

Abstract: An adequate understanding of the mechanisms involved in the structural stabilization of soil by different sources of organic matter is needed to help design management strategies aimed at maintaining a stable soil structure. The objective of this study was to identify mechanisms involved in soil structure stabilization by paper sludge application, either by increasing the soil resistance to external stresses (aggregate stability) or by decreasing the magnitude of the external stresses (diminution of the wettin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…water stable aggregate or benzene stable aggregated) and also the information provided about application rates. Paper sludge has generally been shown to have a positive effect on aggregation (Nematic et al, 2000). Nematic et al (2000), compared composted and uncomposted paper sludge and composted municipal wastes on aggregation stability have shown positive (Aggelides and Londra 2000;Albiach et al, 2001).…”
Section: Residual Effect Of Organic Waste Amendments On Crop Yield Anmentioning
confidence: 99%
See 1 more Smart Citation
“…water stable aggregate or benzene stable aggregated) and also the information provided about application rates. Paper sludge has generally been shown to have a positive effect on aggregation (Nematic et al, 2000). Nematic et al (2000), compared composted and uncomposted paper sludge and composted municipal wastes on aggregation stability have shown positive (Aggelides and Londra 2000;Albiach et al, 2001).…”
Section: Residual Effect Of Organic Waste Amendments On Crop Yield Anmentioning
confidence: 99%
“…Paper sludge has generally been shown to have a positive effect on aggregation (Nematic et al, 2000). Nematic et al (2000), compared composted and uncomposted paper sludge and composted municipal wastes on aggregation stability have shown positive (Aggelides and Londra 2000;Albiach et al, 2001). Carter and Gregorich(1996) reported that turnover time of organic matter in aggregate could be much longer than that of litter remained without aggregation.…”
Section: Residual Effect Of Organic Waste Amendments On Crop Yield Anmentioning
confidence: 99%
“…The main drawback of this solution is concern about the transfer of pollutants, especially Pb, from wastes to groundwater and runoff and subsequently to organisms (Battaglia et al, 2007;Calace et al, 2005). Few studies have addressed the long-term sustainability of reclamation by organic waste (Bacholle et al, 2006;Nemati et al, 2000;Vetterlein and Hüttl, 1999;Villar et al, 1997). Key concerns in this regard are that composting is not widely practiced or integrated in policies worldwide, and the amount of available organic waste varies widely within and between cities (Narkhede et al, 2010).…”
Section: Existing Solutions For Providing Functional Soils In Citiesmentioning
confidence: 99%
“…The main drawback of this solution is concern about the transfer of pollutants, especially Pb, from wastes to groundwater and runoff and subsequently to organisms (Battaglia et al, 2007;Calace et al, 2005). Few studies have addressed the long-term sustainability of reclamation by organic waste (Bacholle et al, 2006;Nemati et al, 2000;Vetterlein & Hüttl, 1999;Villar et al, 1997). Key concerns in this regard are that composting is not widely practiced or integrated in policies worldwide and the amount of available organic waste varies widely within and between cities (Narkhede et al, 2010).…”
Section: Existing Solutions To Provide Functional Soils In Citiesmentioning
confidence: 99%